Geophysics for petroleum engineers - Dasgupta, Shivaji N.; Aminzadeh, Fred (Handbook of petroleum exploration and production ;, 2013)
Geophysics for Petroleum Engineers focuses on the applications of geophysics in addressing petroleum engineering problems. It explores the complementary features of geophysical techniques in better understanding, characterizing, producing and monitoring reservoirs. This book introduces engineers to geophysical methods so that they can communicate with geophysicist colleagues and appreciate the benefits of their work. These chapters describe fundamentals of geophysical techniques, their physical bases, their applications and limitations, as well as possible pitfalls in their misuse. Case study examples illustrate the integration of geophysical data with various other data types for predicting and describing reservoir rocks and fluid properties. The examples come from all over the world, with several case histories from the fields in the Middle East. Introduces geophysical methods to engineersHelps understanding, characterizing, producing and monitoring of geophysical techniques. Updates the changing needs of reservoir engineering.